Mobile Controlled Land Mine Detecting Robot with Message Alert - K.Srinivasulu1, Dr.Kirupa ganapathy2 (International Journal of Advanced Science and Technology, 2020)
This project is mainly used for finding metal elements. In army for detecting the land minesthe soldiers use handled metal detector so that sometimes the land mine was explode. That way thesoldiers are died. For solving this problem, this project is used .This project have advanced alert systemthat is message alert. This is designed by using ‘Arduino’ technology. In this project the metal detectoris connected to Arduino board, the hole circuit is placed on one robot car. This car is controlled byBluetooth by using radio technology with Bluetooth module. When the metal detector detects the metalthe Arduino send message to mobile by using GSM module. This project obtains only one Arduino boardbecause all three application programs are merged in only one board. Using this project find valuabletreasures at under land and covered areas and also detects the land mines at unmanned areas. Thisproject also used for security purposes.